Lilly's Big Day - Henkes, Kevin ([New York] : Greenwillow Books, 2006)
When her teacher announces that he is getting married, Lilly the mouse sets her heart on being the flower girl at his wedding.
Keywords: Mice -- Juvenile fiction; Weddings -- Juvenile fiction; Teachers -- Juvenile fiction; Mice -- Fiction; Weddings -- Fiction; Teachers -- Fiction